2008
DOI: 10.1111/j.1399-3054.2007.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzymatic activity is linked to waterlogging stress tolerance in citrus

Abstract: Soil flooding constitutes a seasonal factor that negatively affects plant performance and crop yields. In this work, the relationship between oxidative damage and flooding sensitivity was addressed in three citrus genotypes with different abilities to tolerate waterlogging. We examined leaf visible damage, oxidative damage in terms of malondialdehyde (MDA) concentration, leaf proline concentration, leaf and root ascorbate and glutathione contents and the antioxidant enzyme activities superoxide dismutase (EC 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
160
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(186 citation statements)
references
References 30 publications
19
160
3
4
Order By: Relevance
“…The enhanced stress induces activities of these enzymes in seedlings subjected to soil flooding to protect them from the stress (Liu et al, 2006;Arbona et al, 2008;BaileySerres and Voesenek, 2008). Several enzymes (superoxide dismutase, catalase, peroxidase, and glutathione peroxidase) scavenging ROS and low molecular mass antioxidants (ascorbate, glutathione, phenolics, and tocopherols) extend tolerance against stress (Noctor and Foyer, 1998;Blokhina et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced stress induces activities of these enzymes in seedlings subjected to soil flooding to protect them from the stress (Liu et al, 2006;Arbona et al, 2008;BaileySerres and Voesenek, 2008). Several enzymes (superoxide dismutase, catalase, peroxidase, and glutathione peroxidase) scavenging ROS and low molecular mass antioxidants (ascorbate, glutathione, phenolics, and tocopherols) extend tolerance against stress (Noctor and Foyer, 1998;Blokhina et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The degree of increase in total SOD activity in wheat roots under anoxia was reported to be positively correlated with duration of anoxia (Van Toai and Bolles 1991). Arbona et al (2008) reported that water-logging induced positive antioxidant response in citrus cultivars Carrizo citrange and Citrumelo CPB 4475 might be responsible for a higher tolerance to flooding stress, whereas the susceptibility of Cleopatra mandarin could be due to less activity of antioxidant enzymes. Wang and Jiang (2007) reported that SOD and APX were mainly involved in water-logging induced antioxidant responses, and the partial water-logging could also significantly affect root antioxidant activities, particularly in water-loggingsensitive cultivar.…”
Section: Introductionmentioning
confidence: 99%
“…According to Bakh-Engler theory, peroxidation processes occur permanently and unavoidably in the cells of living organisms. The relationship between the concentrations of hydrogen peroxide and MDA in roots and leaves of various plants exposed to soil flooding was repeatedly demonstrated (Asada, 2006) and the existence of a direct relationship between stress sensitivity and the early accumulation of MDA was shown (Arbona et al, 2008). Usually soil hypoxia increased the MDA concentration, especially in intolerant species (Chen and Qualls, 2003;Yordanova and Popova, 2007).…”
Section: Fig 1 Alcohol Dehydrogenase (Adh) Activity In Roots Ofmentioning
confidence: 98%
“…The developmental expression and tissue-specific responses of each gene member to hypoxic stress was demonstrated on various species (Garnczanska 2002;Preiszner et al, 2001;Wignarajah et al, 2006). Agrophys., 2012Agrophys., , 26, 347-353 doi: 10.2478 (Arbona et al, 2008, Balakhnina et al, 2009 (Asada, 2006;Blokhina et al, 2002). The pertinent literature presents data on correlation of the degree of resistance to extreme temperatures, salinity, drought and other stress factors with the free proline concentration in the plant tissues.…”
Section: Introductionmentioning
confidence: 99%